2017
DOI: 10.1002/ceat.201700093
|View full text |Cite
|
Sign up to set email alerts
|

Process Intensification of n‐Butane Oxidation to Maleic Anhydride in a Millistructured Reactor

Abstract: Dedicated to Professor Rüdiger Lange on the occasion of his 65th birthdayThe oxidation of n-butane to maleic anhydride over an industrial vanadyl pyrophosphate oxide catalyst was investigated experimentally in millistructured reactors with varying slit widths to investigate the process intensification potential of this reaction. Although the smaller reactor behaved isothermally, even in the presence of high n-butane concentrations, moderate hot spots never exceeding more than 15 K above the salt bath temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…As already shown by Hofmann for a reactor with a slit width of 1.5 mm instead of the 1.65 mm used here, the reactor behaves almost isothermally. Even at high space velocities of up to 4800 m N 3 m −3 h −1 and over 90 % conversion, the measured temperature of the catalyst bed is at maximum 5 K above the temperature of the surrounding salt bath.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…As already shown by Hofmann for a reactor with a slit width of 1.5 mm instead of the 1.65 mm used here, the reactor behaves almost isothermally. Even at high space velocities of up to 4800 m N 3 m −3 h −1 and over 90 % conversion, the measured temperature of the catalyst bed is at maximum 5 K above the temperature of the surrounding salt bath.…”
Section: Resultssupporting
confidence: 66%
“…These low hot spots compared to industrial reactors allow an operation at higher butane concentrations than the usual maximal 1.8 % in industry. As shown by Hofmann , a runaway of the reactor does not occur even at concentrations significantly above (up to 4.5 %) the lower explosion limit. To ensure comparability with industrial conditions, the concentration of butane was limited to 2.1 % for the present work.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Experiments were conducted in a slit fixed-bed reactor (hereafter referred to as μ-reactor) originally developed by Hofmann et al 29 and further improved by Muller et al 27 as shown in Figure 1. Only a brief summary of the experimental setup is given here; the authors refer the reader to the Supporting Information (chapters S1−S3) and the original publications by Hofmann et al 29 and Muller et al 27 for a more detailed description.…”
Section: ■ Methodsmentioning
confidence: 99%